Revolution and International Politics : Second Edition. - Calvert, Peter (History and Politics in the 20th Century: Bloomsbury Academic., 2016)
"This book aims to present an analysis of the role of revolution in international politics. Concerning itself with the time frame from the French Revolution up to the fall of the Iron Curtain, this book covers the study of revolution itself, the importance of globalisation, interdependence and non-state actors and the change in the nature of international politics theory."--Bloomsbury Publishing